Treatment of Nontuberculous Mycobacterial Pulmonary Disease: An Official ATS/ERS/ESCMID/IDSA Clinical Practice Guideline - Daley, Charles L; Iaccarino, Jonathan M; Lange, Christoph; Cambau, Emmanuelle; Wallace, Jr, Richard J; Andrejak, Claire; Böttger, Erik C; Brozek, Jan; Griffith, David E; Guglielmetti, Lorenzo; Huitt, Gwen A; Knight, Shandra L; et al. (Clinical infectious diseases, 2020)
Nontuberculous mycobacteria (NTM) represent over 190 species and subspecies, some of which can produce disease in humans of all ages and can affect both pulmonary and extrapulmonary sites. This guideline focuses on pulmonary disease in adults (without cystic fibrosis or human immunodeficiency virus infection) caused by the most common NTM pathogens such as Mycobacterium avium complex, Mycobacterium kansasii, and Mycobacterium xenopi among the slowly growing NTM and Mycobacterium abscessus among the rapidly growing NTM. A panel of experts was carefully selected by leading international respiratory medicine and infectious diseases societies (ATS, ERS, ESCMID, IDSA) and included specialists in pulmonary medicine, infectious diseases and clinical microbiology, laboratory medicine, and patient advocacy. Systematic reviews were conducted around each of 22 PICO (Population, Intervention, Comparator, Outcome) questions and the recommendations were formulated, written, and graded using the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) approach. Thirty-one evidence-based recommendations about treatment of NTM pulmonary disease are provided. This guideline is intended for use by healthcare professionals who care for patients with NTM pulmonary disease, including specialists in infectious diseases and pulmonary diseases.